Ustaz Abdul Shomad's Da'wah Rhetoric in Attracting Public Interest in Listening to Da'wah Through YouTube Media - Siregar, Muhammad Alfarizi; Faridah, Faridah (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
One effective way to convey da'wah in the era of increasingly developing technology is to use the media as a channel for da'wah. Apart from that, the art of conveying da'wah also impacts whether or not the da'wah message reaches the da'wah partners easily. This article discusses how Ustaz Abdul Shomad's preaching rhetoric attracts people's interest in listening to his preaching via YouTube. This type of writing is descriptive qualitative research. Data was collected using direct observation/observation by watching Ustaz Abdul Shomad's preaching broadcasts via Ustadz Abdul Shomad Official YouTube videos. Another technique used is library research, namely collecting data through books, journals, and previous research. Data analysis was done using the media analysis method on Ustadz Abdul Shomad Official's YouTube account. The results of the research answered that to attract people's interest in watching preaching on YouTube media, Ustaz Abdul Shomad preached using a loud language style, a rising and falling tone and intonation, choosing everyday language that was easy for all groups to understand but still educational, and facial expressions. as well as body movements that are appropriate to the material discussed.